British Gynaecological Cancer Society/British Association of Gynaecological Pathology consensus for germline and tumor testing forBRCA1/2 variants in ovarian cancer in the United Kingdom. Issue 2 (February 2021) - Sundar, Sudha; Manchanda, Ranjit; Gourley, Charlie; George, Angela; Wallace, Andrew; Balega, Janos; Williams, Sarah; Wallis, Yvonne; Edmondson, Richard; Nicum, Shibani; Frost, Jonathan; Attygalle, Ayoma; et al.
ABSTRACT : N/A: The British Gynecological Cancer Society and the British Association of Gynecological Pathologists established a multidisciplinary consensus group comprising experts in surgical gynecological oncology, medical oncology, genetics, and laboratory science, and clinical nurse specialists to identify the optimal pathways to BRCA germline and tumor testing in patients with ovarian cancer in routine clinical practice. In particular, the group explored models of consent, quality standards identified at pathology laboratories, and experience and data from pioneering cancer centers. The group liaised with representatives from ovarian cancer charities to also identify patient perspectives that would be important to implementation. Recommendations from these consensus group deliberations are presented in this manuscript.